CFD Approach for Non-Ideally Mixed Bioreactor Modeling - Liew, Emily; Kumar, Perumal; Samyudia, Yudi (CUTSE 2009, 2009)
In this paper, we address the progress, challenges and prospect of modeling mixing in bioreactor by the utilization of Computational Fluid Dynamics (CFD). Efficient operation of bioreactor is essential in the biotechnological process, not only to ensure good yield but also to maintain consistent product quality. Process modeling technique has frequently been adopted in the bioreactor design, optimization and control as well as in scale-up process. One of the critical issues in bioreactor modeling is the need to overcome the mass and heat transfer limitations imposed on the bioreactor performance, particularly the close interaction between fluid flow and the biological reactions. CFD can be applied to overcome this obstacles by integrating the flow rates between adjacent zones, and fluid mechanical quantities, as the integration of mixing phenomena into the bioreactor modeling is considered a vital aspect in the efficient design and scale-up of bioreactor system.